HUBUNGAN KONSENTRASI MALONDIALDEHIDA, GLUKOSA DAN TOTAL KOLESTEROL PADA TIKUS PUTIH YANG DIINJEKSI DENGAN STREPTOZOTOCIN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Diabetes mellitus is a major source of morbidity in developed countries. The morbidity and mortality are increased in patients with diabetes mellitus compared with the general population. Relationship between high sugar or fat consumption with the increasing of glucose or blood cholesterol concentration has been well understood, but the mechanism of diabetes mellitus as a result of streptozotocin injection and its relation with glucose and cholesterol concentration still need to be investigated. So far, many research mention that streptozotocin causes only the damage of a cell of pancreas which that directly relates to metabolism of blood sugar. The purpose of the research is to investigate the mechanism of pancreas damage in its relation with lipid peroxidation. Sixteen male Wistar rats, 200 grams of bodyweight were used as animal models. Rats were divided into two groups of eight animals each. Group I was not injected with streptozotocin, while Group II is injected intraperitoneally with streptozotocin 50 mg/kg BW.Three days after the injection, blood samples were taken intracardially for Malondialdehida (MDA), glucose and total cholesterol analysis. A one-way analysis of variance showed that there were significance differences between Group I and II (P